Associations between salivary cytokines and periodontal and microbiological parameters in orthodontic patients. Issue 10 (12th March 2021) - Chen, Yong; Wong, Wing Kit; Seneviratne, Jayampath C.; Huang, Shuying; McGrath, Colman; Hagg, Urban
Abstract : Abstract: Orthodontic treatment can lead to microbial-induced gingival inflammation and aseptic periodontal inflammations. The aim of this study was to investigate the relationship between salivary pro-inflammatory cytokines levels with gingival health status and oral microbe loads among patients undergoing orthodontic treatment. The present investigation was a cross-sectional study among a sample of 111 consecutive orthodontic patients (mean age 18.4 ± 4.4 years). Clinical examinations were conducted to assess the gingival health status employing the Modified Gingival Index, Gingival Bleeding Index, and Plaque Index. Salivary microbiological assessments of total aerobic and anaerobic bacteria count, streptococci count, and lactobacilli count were undertaken. Saliva immunological assessments included Interleukin-1Beta (IL-1β) and macrophage migration inhibitory factor (MIF) ELISA assays. The mean ± standard deviation of salivary IL-1β was 83.52 ± 85.62 pg/ml and MIF was 4.12 ± 0.96 ng/ml. Moderate positive correlations were found between salivary IL-1β levels and total aerobic and anaerobic bacteria count, streptococci count, and lactobacilli count ( r  = 0.380–0.446, P  < .001), and weak positive correlations between salivary MIF levels and total salivary aerobic and anaerobic bacteria counts ( r  = 0.249–0.306, P  < .01) were observed. A positive correlation was found between salivary IL-1β levels and Bleeding Index ( r  = 0.216, P  < .05). The level of salivary IL-1β positively correlates with oral bacterial load among orthodontic patients; the relationship between inflammatory cytokines and oral microflora deserved further study.